2018
DOI: 10.4236/oalib.1104521
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Use of Modern Family Planning among Northern Nigerian Women: A Secondary Analysis of 2013 NDHS

Abstract: Introduction: Family planning allows people to attain their desired number of children and determine the spacing of pregnancies. It is achieved through use of contraceptive methods and the treatment of infertility. The aim of this study was to determine various factors that influenced the uptake of modern family planning among women of reproductive age in Northern Nigeria. Methodology: The study used data obtained from Nigeria Demographic and Health Survey (NDHS) 2013. Factors considered were drawn from the da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…It has been reported that the South-West geopolitical zone has the highest prevalence of use of modern family planning methods and that the national average was 9.68% [12]. Among Northern Nigerian women, only 5.33% use modern family planning methods [13]. The great difference between the South-Western women and the Northern women may be because of their differences in education.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the South-West geopolitical zone has the highest prevalence of use of modern family planning methods and that the national average was 9.68% [12]. Among Northern Nigerian women, only 5.33% use modern family planning methods [13]. The great difference between the South-Western women and the Northern women may be because of their differences in education.…”
Section: Discussionmentioning
confidence: 99%
“…The great difference between the South-Western women and the Northern women may be because of their differences in education. While 89% of the South-Western women had formal education, only 34.1% of the Northern Nigerian women had formal education [13]. A study among Nigerian women had shown that those who had secondary education or more were 2.9 times more likely than those who had primary education or less to use modern family planning methods [12].…”
Section: Discussionmentioning
confidence: 99%